Education for Sustainable Development: Tanjung Bumi Batik-based Teaching Materials - Wiwin Puspita Hadi; Aida Fikriyah; Nur Qomaria; Mega Whinalia; Faizatul Holidiah; Winda Afrida; Ajeng Wahyu Martareza; Nur Fajrina Safira (Indonesian Journal of Mathematics and Natural Science Education, 2025)
Integrating local wisdom into Education for Sustainable Development (ESD) is academically important as it connects scientific concepts with cultural practices, thereby promoting contextual learning. However, ESD-based teaching materials that specifically integrate batik-based local wisdom remain limited, particularly in linking batik cultural practices with scientific concepts and sustainability principles in learning. Therefore, this study aims to develop and evaluate the feasibility of teaching materials based on Tanjung Bumi Madura batik local wisdom to support ESD. This study employed a Research and Development (R&D) approach using the 4D model (define, design, development, without the disseminate stage). Feasibility was assessed through expert validation, while readability and student responses were collected using questionnaires. The results show that the developed teaching materials achieved a mode score of 4 (very valid) and reliable based on percentage of agreement (≥ 75%). The readability percentages were 78.33%, 90.20%, and 94.24%, while student responses were 81.47%, 94.25%, and 90.20%, all categorized as very good. Based on these findings, the teaching materials are considered feasible for use in science learning. This study provides empirical evidence supporting the feasibility of ESD-based teaching materials integrating batik-based local wisdom for use in science learning